Implementing a community-based project in an EFL rural classroom - Bolaños Saenz, Francis; Florez, Karol; Gomez, Tatiana; Ramirez Acevedo, Mary; Tello Suarez, Sandra (Colombian Applied Linguistics Journal, 2018)
Educational work within a social perspective has been a matter of interest and discussion of researchers and teachers whose work is framed within a pedagogy for social justice, community pedagogies, and critical literacy (Comber & Kamler, 2004). A social perspective to education requires that teachers in rural and urban contexts become socially and culturally committed to addressing the learning needs of EFL in classrooms. This article shares the outcomes of the experience of five pre-service teachers who explored a local community of a Colombian rural school with a group of 36 ninth-grade EFL students. The pre-service teachers crafted a project-based curriculum taking the community as the content that would empower the students to explore social and cultural aspects of their community while promoting their EFL learning. Data were collected during the four-month period of the pedagogical intervention through interviews, observations and students’ and teachers’ written reflections. The high school students carried out a series of tasks aimed at raising their awareness about their identity, questioning their surroundings and increasing their self-confidence while using their knowledge of English.